Genetic drift in hypervariable region 1 of the viral genome in persistent hepatitis C virus infection. - Kato, N (1994)
The hypervariable region 1 (HVR1) of the putative second envelope glycoprotein (gp70) of hepatitis C virus (HCV) contains a sequence-specific immunological B-cell epitope that induces the production of antibodies restricted to the specific viral isolate, and anti-HVR1 antibodies are involved in the genetic drift of HVR1 driven by immunoselection (N. Kato, H. Sekiya, Y. Ootsuyama, T. Nakazawa, M. Hijikata, S. Ohkoshi, and K. Shimotohno, J. Virol. 67:3923-3930, 1993). We further investigated the sequence variability of the HCV genomic region that entirely encodes the envelope proteins (gp35 and gp70); these sequences were derived from virus isolated during the acute and chronic phases of hepatitis in one patient, and we found that HVR1 was a major site for genetic mutations in HCV after the onset of hepatitis. We carried out epitope-mapping experiments using the HVR1 sequence derived from the acute phase of hepatitis and identified two overlapping epitopes which are each composed of 11 amino acids (positions 394 to 404 and 397 to 407). The presence of two epitopes within HVR1 suggested that epitope shift happened during the course of hepatitis. Four of six amino acid substitutions detected in HVR1 were located within the two epitopes. We further examined the reactivities of anti-HVR1 antibodies to the substituted amino acid sequences within the two epitopes. HVR1 variants in both epitopes within the HVR1 escaped from anti-HVR1 antibodies that were preexisting in the patient's serum.